Study of mineral aerosols in fine (PM 2.5 ) and coarse (PM 10 ) atmospheric particles over a world heritage site at Agra, India. (24th December 2014) - Pipal, Atar Singh; Satsangi, P. Gursumeeran; Tiwari, Suresh; Taneja, Ajay
PM2.5 and PM10 samples were collected at different sites from Agra to see their monthly and seasonal trends along with associated mineral aerosols. Annual mean mass concentrations of PM2.5 and PM10 over Agra were 104.25 and 261.89 µg/m 3 respectively. The monthly average varied from 26.94 to 211.56 µg/m 3 and 126.05 to 474.31 µg/m 3 in fine and coarse particles at traffic site while at semirural site it varied from 50.44 to 275.99 and 93.86 to 528.33 µg/m 3 in fine and coarse respectively. Concentrations of crustal elements indicate that calcium was abundant among the elements in mineral dust. Significant correlation coefficient (r = 0.51–0.87) was observed among the crustal elements indicating the origin of these elements from similar type of sources at semirural site. Enrichment factor analysed found that the origin of these elements is from crust and anthropogenic activities as well as local and transported sources.